The Babeldaob road: the impact of road construction on rural labor force outcomes in the Republic of Palau - Randall K. Q. Akee (Institute for the Study of Labor (IZA), 2006)
This research examines the impact of road construction on rural labor force outcomes in a developing country. A new road built in the Republic of Palau links formerly inaccessible rural areas to more urban wage sector employment. We use two censuses conducted five years apart which perfectly bracket the road construction period. The data allow us to identify households that moved in the intervening five year period, thereby correcting any endogenous movement attributable to the road construction. Utilizing a difference-in-difference regression strategy and matched panel data, we find that households impacted by the new road construction tend to increase their wage sector employment, decrease their self-employment in agriculture, decrease the number of international migrants sent abroad and increase their ownership of automobiles. The findings also show that inequality decreases both within and between regions. The impact of road construction on average household wages and income is negligible.
urn:nbn:de:101:1-20080702289
Keywords: 330